Scientific mapping of the nexus between entrepreneurial orientation and environmental sustainability: bibliometric analysis - Tadesse Weyuma Bulto; Tadesse Weyuma Bulto; Abdella Kosa Chebo; Abdella Kosa Chebo; Hailu Fufa Regassa; Birhanu Chalchisa Werku; Birhanu Chalchisa Werku; Helmut Kloos (Frontiers in Sociology)
Entrepreneurial orientation (EO) and environmental sustainability (ES) has recently become the subject of extensive research. The objective of this paper is to comprehensively analyze of EO and ES by conducting a bibliometric network and systematic review analysis of over ten years of publications. A total of 390 articles were identified using the Scopus and Mendeley search engines. One hundred-eighteen articles published in 53 journals between 2012 and 2021 were identified for analysis. Association analysis was conducted by author, co-author, and keyword, as well as keyword analysis by title and abstract fields, abstract field, and title field words with the highest frequency and highest relevance score under the binary counting approach. Performance, entrepreneurial orientation, relationship, entrepreneurship, entrepreneur, and business keywords were the most dominant occurrences in the abstracts. Key topics included models for entrepreneurial orientation; environmental sustainability was potentially more comprehensive in understanding the review work. This comprehensive review holds substantial theoretical significance for advancing the agenda of ecological entrepreneurial orientation and environmental sustainability. The findings of the study will help academics and researchers to identify future research directions and subject areas.